Breeding value of new genetic sources of bread wheat resistance to fungal and viral diseases - Motsnyi, I.; Fanin, Ya.; Molodchenkova, O.; Balvinska, M.; Dashchenko, A.; Mishchenko, I.; Dunich, A.; Mishchenko, L. (Quarantine and plant protection, 2025)
Goal. Evaluation of the best advanced introgression wheat lines with different levels of resistance to fungal and viral diseases by yield performance and quality parameters. Methods. The field research was conducted on the experimental fields of the PBGI-NCSCI in 2020—2024. The study involved 18 introgression lines of different origin. The lines were studied for yield, protein content, sedimentation values and resistance to rust diseases, powdery mildew and barley yellow dwarf virus (BYDV) using conventional methods; the data were processed by analysis of variance. Cultivars that are most common in southern Ukraine and are zonal standards of yield and adaptability were used as controls. Results. The studied introgression lines have showed different responses to disease infection. Most of the lines were resistant to rust species, but affected by BYDV and Septoria leaf blotch. In some lines, high group resistance to diseases, conferred by a combination of wheat and alien genes for resistance, was observed. The studied lines were predominantly inferior to the most yielding standard cultivars Kuyalnyk and Shchedristʹ by 3.6—28.5% in terms of yield, but prevailed or had the same yield compared to the other two standards (Hoduvalʹnytsya and Koloniya). Some lines have been identified to have yield results at the level of the most productive standard cultivars across the years. Almost half of the studied lines accumulated more protein content than the standards regardless on the year, but were inferior to the standards in terms of protein yield due to lower grain yield. Conclusions. A significant positive effect of alien disease resistance genes on protein content, weight of 1000 grains and sedimentation value was found according to the results of the study. The studied introgression lines can be considered as donors of economically valuable traits and be involved in breeding programs for wheat improvement.